Analisis Standarisasi Penilaian Perbankan BI (Model Camel) dan Prediksi Kebangkruta Bank (Model Z-Score Altman) - Ilham Tri Murdo (Sekolah Tinggi Ilmu Ekonomi SBI, 2011)
In Indonesia, a bank rating is typically measured using CAMEL financial ratio model. indicators of bankruptcy can be seen through the financial information contained in financial statements, and predictions of the potential bankruptcy that may be experienced by the company to use the altman Z-Score model. the problems examined in this research is whether there are correlations between banking standardization assessment using financial ratios of CAMEL model to predict banking bankruptcy using the method of Altman method. this research is to obtain empirical evidence of the existence of correlations between the banking systems according to the assessment using financial ratio analysis of CAMEL model with bank bankrupty prediction models b using analysis of Altman Z-Score. The Samples in this reserch are 20 banking companies listed in Indonesia stock exchange in the year 2005-2009. Two variables are examined in this reserch, namely the standardization of banking assessment (Capital, CAR, CAP, CAD, NPM, tbp, ROA, BOPO, LQ, and LDR) and Indonesian banking bankruptcy prediction (Altman Z-Score). Data collection tool in this reserch is the method of documentation which is drawn from the banking financial reports and some books that support. Analysis of the data used in this reserach is the analysis of financial ratis models of CAMEL and Altman Z-Score, and statistical analysis of Pearson Product Moment and Multiple Linear Regression. The reserch results showed that the value of cut-off Altman Z-Score increased from the presence status of the banks which went bankrupt in 2005, then there is no longer with the status of bankrupty in 2006-2009 to only 1 bank that went bankrupt status in 2009. The correlation betwen Capital, CAR, CAP, CAAD, NPM, TBP, ROA,BOPO, LQ, and LDR simultaneosly with altman Z-score is positive.and significant. The counted F is 26,020 with a signification of 0,000 smaller than the expected level of significance . This means that the capital, CAR, CAP, CAD, NPM, TBP, ROA, BOPO, LQ, and LDR. Simutaneosly correlated signifiacntly with altman Z-Score. Thus there is a correlation between Standardization Assessment Banking and Bnkruptcy predicton Bank in Indonesia, Where the Capital, CA, CAP, CAD, NPM, TBP, ROA, BOPO, LQ, and LDR is able to explain the changes of altman Z-score 1,6%, while the reset is explained by other factors